The Effect of Teacher Teaching Skills and Student Interest on History Learning Outcomes - Sumyadi, Yadi; Umasih, Umasih; Syukur, Abdul (LPPM Undiksha, 2020)
Learning outcomes have an important role in the learning process. This is because learning outcomes can be used as a benchmark to determine the extent to which students experience changes after receiving their learning experiences, are observed and measured in the form of knowledge, attitudes and skills. This study aims to analyze teaching skills and teacher learning interest towards historical learning outcomes. The research method used in this research is ex post fact, which means after the fact, by taking survey data. The population and sample in this study were high school students. In the data description analysis stage, the writer describes the problems related to student learning outcomes and the observation data of teacher teaching skills in the learning process. The correlation stage consists of the following steps: analysis prerequisite test and hypothesis testing. Based on the data analysis, the regression equation Y = 44.533 + 0.506 x was obtained, meaning that each addition of the teacher's teaching skills variable by one unit, the student learning outcomes variable increased by 0.506 units. So, it can be concluded that there is a relationship between teacher teaching skills and student learning outcomes.